(untitled) (Research, Society and Development, 2020)
The present study aims to understand the social roles of the two important institutions: family and school, and how the learning process is benefited, when have a partnership can be obtained when both are involved in the children learning process, showing the river people of Marajó’s Amazon reality. The same approach was taken at the Escola Municipal de Ensino Infantil e Fundamental Turé, in a class from the fourth year of elementary school. Initially, a bibliographical research was employed, which were studied the following topics: family, school, public politics and the education standards of Marajó’s Amazonian region. Afterwards, empirical data from the direct participative observation, historical life experiences, visualization of student´s notebooks, interviews with the school´s principal and the class teacher. According to the data analyzed, we can affirm that to have a well educational development, it is necessary to have a strict dialogue between family and school. The children´s learning process is directly connected to the way which the family and the school regards the education obtainment.